A HOSPITAL-BASED STUDY ON UTILISING HPLC TO DETECT HB-VARIANTS AND HEMOGLOBINOPATHIES: A RETROSPECTIVE DESCRIPTIVE STUDY. - Kumar, Satish; Agrawal, Rawi; Kumar, Kaushal; Choudhary, Vijayanand (Student's Journal of Health Research Africa, 2023)
Background Hemoglobinopathies are a growing global health issue. These hereditary diseases are most common worldwide. WHO says the Middle East and India have the highest incidence. HPLC is a good way to screen hemoglobin variants such HbF and HbA2. The present study was carried out to diagnose hemoglobinopathies and thalassemias by the use of HPLC in Indira Gandhi Institute of Medical Sciences, Patna, Bihar, India. Materials and Methods A retrospective descriptive research assessed 550 patients for thalassaemia or other hemoglobin structural abnormalities. This investigation included all cases of microcytic hypochromic anemia (MCV< 80 fl, MCH< 27 pg) with a clinical suspicion of hemoglobinopathy that did not respond to usual treatment. The trial excluded patients who had blood transfusions within three months. Results This study included 550 cases, 310 boys and 240 females, aged 2 months to 40 years. HPLC analysis revealed abnormal hemoglobin fractions in 96 cases. One person had delta thalassemia, one had delta with beta-thalassemia, one had hemoglobin D Iran, two had HbE with beta, six had HbE trait, eight (1%) had beta major, and less than 1% had HbE homozygous. Of the cases, 72 (13%) had beta thalassemia. The HPLC pattern was normal in 48%. In all cases, peripheral blood smears showed target cells, microcytosis, and hypochromia. The majority of patients had increased RBCs. Conclusion Hemoglobinopathies can be quickly, accurately, and effectively diagnosed with HPLC. It is a valuable diagnostic technique for beta thalassemia characteristics, particularly in impoverished nations like India where hemoglobinopathies are difficult to identify. Prompt diagnosis could aid in appropriate and targeted treatment. Recommendation This study emphasizes the need of HPLC for hemoglobinopathy diagnosis, especially in high-burden countries like India. HPLC screening and diagnosis can help combat hemoglobinopathies' global health issues by enabling early detection and focused treatment.